Influence of Land Use Changes on Biodiversity Conservation in Coastal Ecosystems - Akinyi, Mirriam (American Journal of Environment Studies, 2024)
Purpose: The aim of the study was to assess the influence of land use changes on biodiversity conservation in coastal ecosystems. Methodology: This study adopted a desk methodology. A desk study research design is commonly known as secondary data collection. This is basically collecting data from existing resources preferably because of its low cost advantage as compared to a field research. Our current study looked into already published studies and reports as the data was easily accessed through online journals and libraries. Findings: Land use changes significantly impact biodiversity conservation in coastal ecosystems, according to recent studies. The conversion of natural habitats such as mangroves, salt marshes, and coastal forests into urban, agricultural, or industrial areas leads to habitat loss and fragmentation, which directly threatens the survival of many species. These changes disrupt ecological processes, such as nutrient cycling and sediment deposition, which are crucial for maintaining the health of coastal ecosystems. Furthermore, altered land use patterns often result in increased pollution, sedimentation, and habitat degradation, further exacerbating the decline of biodiversity. Implications to Theory, Practice and Policy: Meta-population theory, resilience theory and ecosystem services framework may be used to anchor future studies on assessing the influence of land use changes on biodiversity conservation in coastal ecosystems. Implement ecosystem-based management approaches that consider the interconnectedness of ecological processes and human activities in coastal areas. Advocate for the implementation of spatial planning measures, such as marine spatial planning and coastal zoning, to guide land use decisions and minimize conflicts between conservation and development objectives.